2019
DOI: 10.1021/acs.jpcc.9b09335
|View full text |Cite
|
Sign up to set email alerts
|

Red Thermally Activated Delayed Fluorescence and the Intersystem Crossing Mechanisms in Compact Naphthalimide–Phenothiazine Electron Donor/Acceptor Dyads

Abstract: Controlling of the electronic coupling between electron donor and acceptor subunits in a dyad is pivotal for the development of novel organic materials, for instance, thermally-activated delayed fluorescence (TADF) materials and triplet photosensitizers. Herein we prepared two compact electron donor/acceptor dyads based on phenothiazine (PTZ) and naphthalimide (NI) with different conformation restrictions induced by the CN (NI-N-PTZ) or CC (NI-C-PTZ) linkers. The effect of electronic coupling (matrix element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
168
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(211 citation statements)
references
References 106 publications
24
168
10
Order By: Relevance
“…On the other hand, the RP‐ISC in compact electron donor–acceptor dyads is inhibited, due to the large electronic coupling between the donor and acceptor moieties. However, if the electron donor and acceptor are in orthogonal geometry, the triplet exited state will be populated through spin–orbit charge‐transfer ISC (SOCT‐ISC) [44, 53–57] . In this process, CR between donor and acceptor produces a large change in molecular orbit angular momentum.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the RP‐ISC in compact electron donor–acceptor dyads is inhibited, due to the large electronic coupling between the donor and acceptor moieties. However, if the electron donor and acceptor are in orthogonal geometry, the triplet exited state will be populated through spin–orbit charge‐transfer ISC (SOCT‐ISC) [44, 53–57] . In this process, CR between donor and acceptor produces a large change in molecular orbit angular momentum.…”
Section: Introductionmentioning
confidence: 99%
“…[38] In some compact electron donor/acceptor dyads, we observed 3 CT state with time-resolved electron paramagnetic resonance (TREPR) spectroscopy, which is rare. [39,40] Another issue concerning the SOCT-ISC is that although it was proposed that upper triplet state should be involved in the SOCT-ISC, [26] yet no experimental evidence has been reported for this postulate. Hence, much room is left for the investigation of SOCT-ISC and more dyads to unravel the relationship of the dyad molecular structures and the SOCT-ISC efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, NTO simulations suggested that TrzCNTrx2 includes more CT character, which reduced the Δ E ST and accelerates RISC process. [ 20 ] The TRPL decay curves of the delayed and prompt fluorescence are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…[ 5–8 ] Whereas, the electron donors have been rather limited as acridine, carbazole, and phenothiazine derivatives. [ 1,8–20 ] Therefore, the development of new electron donors is urgently necessary. Particularly, it is important to develop a donor with a rigid structure because the use of rigid donor moiety was effective to improve EQE and reduce efficiency roll‐off at high luminance.…”
Section: Introductionmentioning
confidence: 99%